2019
DOI: 10.1038/s41467-019-12169-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeated species radiations in the recent evolution of the key marine phytoplankton lineage Gephyrocapsa

Abstract: Phytoplankton account for nearly half of global primary productivity and strongly affect the global carbon cycle, yet little is known about the forces that drive the evolution of these keystone microscopic organisms. Here we combine morphometric data from the fossil record of the ubiquitous coccolithophore genus Gephyrocapsa with genomic analyses of extant species to assess the genetic processes underlying Pleistocene palaeontological patterns. We demonstrate that all modern diversity in Gephyrocapsa (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 85 publications
7
80
1
Order By: Relevance
“…Diversification pulses within the Noelaerhabdaceae, characterized by a gradual increase in maximum sizes and terminated by abrupt declines in size, have been documented across the Neogene (e.g., Beaufort, 1992; 10.1029/2020PA003915 Bollmann et al, 1998;Bolton et al, 2016;Henderiks & Pagani, 2007;Imai et al, 2015;Matsuoka & Okada, 1990;Young, 1990). Recently, Bendif et al (2019) demonstrated that such pulses reflect species radiations (speciation) separated by abrupt extinctions and that the three most recent pulses in the Pleistocene evolution of Gephyrocapsa (including E. huxleyi) are associated with step changes in global SST. These Pleistocene bursts in species diversification ("Matsuoka-Okada cycles") had durations of~0.5 Myr (Bendif et al, 2019), much shorter than those suggested by the Miocene data sets (e.g., Henderiks & Pagani, 2007;Imai et al, 2015;Young, 1990; this study).…”
Section: Evolutionary Overturn and Diversification Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversification pulses within the Noelaerhabdaceae, characterized by a gradual increase in maximum sizes and terminated by abrupt declines in size, have been documented across the Neogene (e.g., Beaufort, 1992; 10.1029/2020PA003915 Bollmann et al, 1998;Bolton et al, 2016;Henderiks & Pagani, 2007;Imai et al, 2015;Matsuoka & Okada, 1990;Young, 1990). Recently, Bendif et al (2019) demonstrated that such pulses reflect species radiations (speciation) separated by abrupt extinctions and that the three most recent pulses in the Pleistocene evolution of Gephyrocapsa (including E. huxleyi) are associated with step changes in global SST. These Pleistocene bursts in species diversification ("Matsuoka-Okada cycles") had durations of~0.5 Myr (Bendif et al, 2019), much shorter than those suggested by the Miocene data sets (e.g., Henderiks & Pagani, 2007;Imai et al, 2015;Young, 1990; this study).…”
Section: Evolutionary Overturn and Diversification Pulsesmentioning
confidence: 99%
“…Recently, Bendif et al (2019) demonstrated that such pulses reflect species radiations (speciation) separated by abrupt extinctions and that the three most recent pulses in the Pleistocene evolution of Gephyrocapsa (including E. huxleyi) are associated with step changes in global SST. These Pleistocene bursts in species diversification ("Matsuoka-Okada cycles") had durations of~0.5 Myr (Bendif et al, 2019), much shorter than those suggested by the Miocene data sets (e.g., Henderiks & Pagani, 2007;Imai et al, 2015;Young, 1990; this study). This could be due to a true acceleration of evolutionary rates (and related climatic forcings) during the Pleistocene compared to the Miocene.…”
Section: Evolutionary Overturn and Diversification Pulsesmentioning
confidence: 99%
“…6c). A prime example of this is the comparison between the Helicosphaera genus, with its highly conserved morphology, little phenotypic innovation, low abundances and relatively stable biogeochemical performance; and the Noelaerhabdaceae, with the potential for inter-species hybridization (Bendif et al, 2015) and rapid diversification (Bendif et al, 2019), global dominance in marine phytoplankton communities (Suchéras-Marx and Henderiks, 2014; Fig. S3) and a range of possible biogeochemical outputs ( Fig.…”
Section: Biogeochemical Implications Of Phenotypic Evolutionmentioning
confidence: 99%
“…To observe the developmental pattern of scales in Takifugu species, three closely-related species, one scale-covered (T. niphobles) and two scale-uncovered (T. pardalis and T. snyderi), were obtained by in vitro fertilization and sampled at 1,2,3,5,7,14,21,28,29,56,63, and 101 days post-hatch (dph). Live fish were stained up to 63 dph with 0.1% alizarin red S or 2% cochineal dye (Kiriya Chemical, Osaka, Japan) dissolved in half-strength seawater for 8 hours, washed in half-strength seawater for 10 min, and then euthanized in ice-cold seawater.…”
Section: Developmental Pattern Of Spiny Scalesmentioning
confidence: 99%
“…Classic examples of the rapid radiation include finch birds, silversword plants, anole lizards, threespine sticklebacks, and cichlid fishes [1][2][3][4][5][6]. Recent advances in genomics have enabled the study of the genetic basis of phenotypic evolution associated with rapid adaptation not only in the classic examples but also in many other groups of organisms [7,8]. Interestingly, this line of research also allows investigations into the predictability of evolutionary change [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%